2018
DOI: 10.11604/pamj.2018.31.177.16390
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of dengue virus among children presenting with febrile illness in some public health facilities in Cameroon

Abstract: Introduction A routine diagnosis of Dengue virus (DENV) infection is not usually conducted in hospitals. Because symptoms overlap, many potential febrile illnesses due to DENV may be confused for malaria, typhoid or paratyphoid (enteric) fever. The absence of data on DENV exposure rates among children attending health facilities could undermine management of this disease. This study aimed to investigate the seroprevalence of dengue virus infection in children presenting febrile illness in some pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 39 publications
5
62
2
3
Order By: Relevance
“…The rural and peri-urban habitats were located in Fonakeukeu (05 • All study sites are located in the highland area of western Cameroon that exhibits a sub-tropical climate characterised by two seasons; a dry season of four months (from mid-November to mid-March) and a rainy season of eight months (mid-March to mid-November). The annual average rainfall and temperature of this region are 321 mm and 21.6 °C , respectively [42]. An urban area (Dschang) was defined as a location with more than 1000 persons per km 2 [44].…”
Section: Description Of the Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The rural and peri-urban habitats were located in Fonakeukeu (05 • All study sites are located in the highland area of western Cameroon that exhibits a sub-tropical climate characterised by two seasons; a dry season of four months (from mid-November to mid-March) and a rainy season of eight months (mid-March to mid-November). The annual average rainfall and temperature of this region are 321 mm and 21.6 °C , respectively [42]. An urban area (Dschang) was defined as a location with more than 1000 persons per km 2 [44].…”
Section: Description Of the Study Sitesmentioning
confidence: 99%
“…In addition to the many human cases of arboviruses reported in the different regions of Cameroon; South [36,37], Littoral [38], Centre [39], Southwest [40], Northwest [41], West, Far North and Adamaoua [42], the country is undergoing a rapid increase in urbanisation that is impacting the population dynamics of mosquito species and, subsequently, the risk of arbovirus transmission to humans. Dschang is one such city in Cameroon which has experienced over the past years, a modification of its natural environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,9] and in the Fako Division [4]. Furthermore, a recent study found 11.7% and 10.4% of DENV circulating in Dschang and Bagangté respectively [10], all situated in the western highland. Another study revealed acute dengue in children living in urban and semi-urban areas of Dschang [32].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review, Braack and colleagues [1] Orthobunyavirus genus, Bunyaviridae family. These findings originate from many studies that have investigated the prevalence of arboviruses in Cameroon mainly based on the serodiagnostic of blood samples collected from humans [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Chikungunya Virus and Zika Virus)mentioning
confidence: 99%